Caudate Nucleus Volumes in Frontotemporal Lobar Degeneration: Differential Atrophy in Subtypes - Looi, J.C.L; Lindberg, O; Zandbelt, B.B; Ostberg, P; Andersen, C; Botes, L; Svensson, L; Wahlund, L.-O (American journal of neuroradiology : AJNR, 2008)
Frontostriatal circuits involving the caudate nucleus have been implicated in frontotemporal lobar degeneration (FTLD). We assessed caudate nucleus volumetrics in FTLD and subtypes: frontotemporal dementia (FTD, n = 12), semantic dementia (SD, n = 13), and progressive nonfluent aphasia (PNFA, n = 9) in comparison with healthy controls (n = 27) and subjects with Alzheimer disease (AD, n = 19). Diagnoses were based on accepted clinical criteria. Manual volume measurement of the head and body of the caudate, excluding the tail, was conducted on T1-weighted brain MR imaging scans, using a published protocol, by a single analyst blinded to the diagnosis. Paired t tests (P < .05) showed that the right caudate nucleus volume was significantly larger than the left in controls and PNFA. No hemispheric asymmetry was found in AD, FTD, and SD. Across the groups, there was a positive partial correlation between the left caudate nucleus volume and Mini-Mental State Examination (MMSE) scores (r = 0.393, n = 76, P = .001) with higher left caudate volumes associated with higher MMSE scores. Multivariate analysis of covariance was used to assess the statistical significance between the subject groups (AD, FTD, SD, PNFA, and controls) as independent variables and raw right/left caudate volumes at the within-subject level (covariates: age and intracranial volume; P < .05). Control volume was largest, followed by AD (93% of control volume), SD (92%), PNFA (79%), and FTD (75%). Volume of the head and body of the caudate nucleus differs in subtypes of FTLD, due to differential frontostriatal dysfunction in subtypes being reflected in structural change in the caudate, and is correlated with cognition.